2005
DOI: 10.1103/physrevc.71.024312
|View full text |Cite
|
Sign up to set email alerts
|

New relativistic mean-field interaction with density-dependent meson-nucleon couplings

Abstract: We adjust a new improved relativistic mean-field effective interaction with explicit density dependence of the meson-nucleon couplings. The effective interaction DD-ME2 is tested in relativistic Hartree-Bogoliubov and quasiparticle random-phase approximation (QRPA) calculations of nuclear ground states and properties of excited states, in calculation of masses, and it is applied to the analysis of very recent data on superheavy nuclei.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

34
976
1
8

Year Published

2007
2007
2020
2020

Publication Types

Select...
4
4
2

Relationship

2
8

Authors

Journals

citations
Cited by 804 publications
(1,019 citation statements)
references
References 41 publications
34
976
1
8
Order By: Relevance
“…The RQRPA equations are formulated in the canonical single-nucleon basis of the RHB model, by employing effective Lagrangians with density-dependent meson-nucleon couplings [32] in the particle-hole channel and the finite-range Gogny interaction [34] in the pairing channel. The present calculation of the isoscalar monopole response is carried out using the density-dependent meson-exchange effective Lagrangian DD-ME2 [35].…”
Section: Quasiparticle Random Phase Approximationmentioning
confidence: 99%
“…The RQRPA equations are formulated in the canonical single-nucleon basis of the RHB model, by employing effective Lagrangians with density-dependent meson-nucleon couplings [32] in the particle-hole channel and the finite-range Gogny interaction [34] in the pairing channel. The present calculation of the isoscalar monopole response is carried out using the density-dependent meson-exchange effective Lagrangian DD-ME2 [35].…”
Section: Quasiparticle Random Phase Approximationmentioning
confidence: 99%
“…(It has, however, recently been shown that the SkP Skyrme model may diverge for some nuclei if calculated to sufficient accuracy [53]). The third self-consistent mean field model considered here belongs to the framework of the relativistic mean field theory (RMF) with the recent DD-ME2 parametrization of the effective interaction [54]. Although in fitting the DD-ME2 parameters the 208 Pb r np value (of 0.20 fm) was used to adjust the interaction parameters, the shape of the neutron distribution was obtained from the calculation.…”
Section: Calculated Mean Field Neutron and Proton Distributionsmentioning
confidence: 99%
“…In this work, we adopt DD-ME2 [29] for the effective interactions between nucleons. The density dependence of coupling constants are obtained based on the Typel-Wolter ansatz [30].…”
Section: Formulationmentioning
confidence: 99%